Genetic and Virulence Characteristics of a Hybrid Atypical Enteropathogenic and Uropathogenic Escherichia coli (aEPEC/UPEC) Strain - Valiatti, Tiago B.; Santos, Fernanda F.; Santos, Ana C. M.; Nascimento, Júllia A. S.; Silva, Rosa M.; Carvalho, Eneas; Sinigaglia, Rita; Gomes, Tânia A. T. (Frontiers in Cellular and Infection Microbiology, 2020)
Hybrid strains of Escherichia coli combine virulence traits of diarrheagenic (DEC) and extraintestinal pathogenic E. coli (ExPEC), but it is poorly understood whether these combined features improve the virulence potential of such strains. We have previously identified a uropathogenic E. coli (UPEC) strain (UPEC 252) harboring the eae gene that encodes the adhesin intimin and is located in the locus of enterocyte effacement (LEE) pathogenicity island. The LEE-encoded proteins allow enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC) to form attaching and effacing (A/E) lesions in enterocytes. We sought to characterize UPEC 252 through whole-genome sequencing and phenotypic virulence assays. Genome analysis unveiled that this strain harbors a complete LEE region, with more than 97% of identity comparing to E2348/69 (EPEC) and O157:H7 Sakai (EHEC) prototype strains, which was functional, since UPEC 252 expressed the LEE-encoded proteins EspB and intimin and induced actin accumulation foci in HeLa cells. Phylogenetic analysis performed comparing 1,000 single-copy shared genes clustered UPEC 252 with atypical EPEC strains that belong to the sequence type 10, phylogroup A. Additionally, UPEC 252 was resistant to the bactericidal power of human serum and colonized cells of the urinary (T24 and HEK293-T) and intestinal (Caco-2 and LS174T) tracts. Our findings suggest that UPEC 252 is an atypical EPEC strain that emerges as a hybrid strain (aEPEC/UPEC), which could colonize new niches and potentially cause intestinal and extraintestinal infections.